Copyright issues related to the digitization of cultural heritage in Croatia - Horvat, Aleksandra knjižničarka (Array, 2010)
A proliferation of the EU programmes and action plans on digitization proves that there is a political will to digitize and make available to the public the rich cultural heritage of Europe. The article tracks the development of these ideas and actions and focuses on one of the obstacles to overcome - the lack of consistency in approaches to intellectual property rights. The aim of the investigation described in the paper has been to find out how copyright issues related to the digitization performed by public institutions such as libraries and archives have been dealt with in Croatia. Information collected from the national electronic portal Croatian Cultural Heritage was further enriched by interviews held with the persons responsible for digitization projects in three major public institutions in the country. A lack of suitable registries or databases with data on the national authors has been noted. Institutions show different approach to digital copies they produce ; some consider themselves to be publishers and rights holders of new digital editions of works, while the others take digitization primarily as a means of protection of originals. As a rule institution have a policy of copyright management, even if a rudimentary one. All institutions provide copyright information, sometimes with a copyright disclaimer. They use watermarking as a technical protection measure. Digitised materials are provided at no cost on the Internet for private use and research. Use of materials for commercial purposes has to be paid for and the institutions look upon it as a source of revenue to fund further digitization activities. The institutions' policy toward derivative works, i.e. offering the opportunity to users to create their own content is yet to be determined.